From the activities of the extension project "Humanization of constitutional civil law: perspectives and challenges": Humanized civil-constitutional law seen in practice - Saionara Macena de Araújo, Jaianny; Correa de Albuquerque da Costa, Ana Paula (Guará Journal, 2019)
Despite the new constitutional configuration, with the enactment of the Federal Constitution of 1988, the Civil Code of 2002 does not regu-late personal rights, although it presents advances when compared with  the subrogated  Civil  Code.  Hence  the  importance  of  the phenomenon of constitutionalisation, specially the Humanization of Civil Law,  which  brought  a  new  way of  facing  private  relations,  hitherto  eminently patrimonialist relations. Considering this, the objective of the  present  study  was  to  describe  the development  of  didactic-in-structional  material, targeted  to  the  dissemination  of  these  rights  within Paraiba's  public  schools  through  cordel  literature and parodies. There was an immediate integration among students and our group, as the music itself brought us closer together. The experience was enriching and rewarding, and it was possible in an effective way to give back  the community XX (to give back somebody something), which is our duty as citizens, but mainly because we have the privi-lege to obtain public higher education.
Keywords: Humanization of Civil-Constitutional Law; Judicial Education; Personal rights; University extension